Analysis Of Environmental Impact With The Life Cycle Assessment (LCA) Method On Tofu Production - Masayu, Rosyidah; Ansyori Masruri; Romyzar Arya Putra; Mayanita; Ananda; Cindy (International Journal of Science, Technology & Management, 2020)
Tofu is a typical Indonesian food. The tofu production process has its own impact on the environment because the rest of the production results in solid and liquid waste. If the processing or utilization of the waste products is not carried out, it will pollute the surrounding environment. The aim of this research is to identify the environmental impact of the tofu production process. The method used in this research is the method of mixed method simapro program assisted 7. From the results showed that the production process knows it can cause environmental pollution, it is seen from the damage category. Score a single score of 4076,345 Pt, with an environmental impact of Human Health of 1701.54 (41.7%), Ecosystem Quality of 1409.057 (34.6%), and Resources of 965.7484 (23.7%). Based on research results of several categories of the study, obtained on alternative improvements to reduce environmental impact by replacing firewood with biogas as fuel. Keywords : Biogas, Life Cycle Assessment , Environmental Pollution, Production Know, SimaPro